Exploring the impact of adenoid obstruction on the human nasal airflow through parallel computational fluid dynamics - Zhengzheng Yan; Xinhong Wang; Rongliang Chen (Engineering Reports)
Abstract Adenoid obstruction is a prevalent condition that can significantly alter nasal airflow patterns, leading to various respiratory symptoms. This study aims to explore the influence of adenoid obstruction on human nasal airflow using computational fluid dynamics (CFD) simulations. We developed a realistic nasal cavity model to simulate both steady‐state inhalation and transient breathing cycles, accounting for various levels of obstruction. The three‐dimensional, incompressible Navier‐Stokes equations were discretized employing a stabilized P1−P1 finite element method on unstructured meshes, along with an implicit second‐order backward differentiation formula. The numerical solution was obtained using a Newton‐Krylov‐Schwarz algorithm‐based parallel solver. Our findings indicate that obstruction of the adenoid cross‐sectional area below 50% minimally affects nasal airflow, whereas noticeable changes occurred as obstructions exceeded the 50% threshold. Complete blockage was observed at levels greater than 70%, and inhalation difficulties could arise even at the 50% obstruction mark during stimulation or extreme inhalation scenarios. These results substantiate the clinical guidelines that advocate a 50% obstruction ratio as the demarcation between conservative treatment and surgery. Furthermore, this study offers valuable insights into the intricate relationship between the adenoid obstruction and nasal airflow, potentially enhancing clinical decision‐making in the diagnosis and treatment of nasal obstruction.